The Personal Resources of Successful Leaders: A Narrative Review - Kenneth Leithwood (MDPI AG, 2023)
Leaders' practices or overt behaviors are the proximal causes of leaders' effects on their organizations; they also dominate the research about successful leadership and often the content of leadership development programs, as well. But knowledge about those practices is, at best, a necessary but insufficient explanation for successful leadership and how it can be developed. This paper explores three categories of "personal leadership resources" that help explain why especially successful leaders behave as they do. These resources are often referred to as "dispositions", a term sometimes considered synonymous with traits, abilities, personal leadership resources and elements of a leader's personal "capital". The focus of this chapter is on three categories of resources (social, psychological and ethical) identified primarily through systematic research methods. For each category, the paper identifies the conceptual lens through which its dispositions are viewed and provides an explanation for how each of the specific dispositions within the category contributes to leaders' success. The paper also reviews a sample of evidence about contributions each disposition makes to leaders' success in achieving valued organizational outcomes. Implications for research and leader development are discussed in the concluding section of the paper.